The Role of Income Volatility and Perceived Locus of Control in Financial Planning Decisions - Peetz, Johanna; Robson, Jennifer; Xuereb, Silas (Frontiers in Psychology, 2021)
Two studies examine whether income volatility might lead to greater personal financial insecurity and might create a decision environment that discourages planning ahead on personal finances. In Study 1 (N = 982), participants who reported more month-to-month variability in their actual income were less likely to have planned for financial contingencies. A lower internal locus of control partially mediated the link between volatility and financial planning decisions in Study 1, and lower internal locus of economic control predicted financial planning decisions independently of volatility. In Study 2 (N = 149), participants who were randomly assigned to receive volatile (vs. stable) payments in a simulated work environment were less likely to save their compensation for this work. Again, lower internal locus of economic control predicted financial planning decisions independently of volatility. This is the first study to demonstrate a causal link between income volatility and financial decisions, specifically a heightened tendency to make short-term financial decisions. Both studies also underlined the importance of internal locus of control for financial planning decisions.